Evaluation of Cu2+ ions adsorption equilibrium in calcined bentonite clay and after treatment with sodium - Soeiro, Thatyana Nunes; De Freitas, Emanuelle Dantas; Maia, Gabriella Simon; Santos, Adriana Barbosa [UNESP]; Vieira, Melissa Gurgel Adeodato; Guirardello, Reginaldo (My University, 2017)
Industrial activities are responsible for the increasing environmental degradation through unsustainable consumption of natural resources and the improper disposal of various wastes. In Brazil, of all generated wastes, effluents containing heavy metals are causing more problems, because they have negative effects on the ecosystem, leading to reduced water quality which harms aquatic life, wildlife, flora, and also human health. Hence, effluents containing heavy metals have to suffer a purification treatment to remove these microcontaminants. There are several processes used to remove metal ions from wastewater, among which adsorption presents greater possibilities of use, because it is very effective in removing heavy metals even in low concentrations. Therefore, this work aims to evaluate the Cu2+ ion adsorption equilibrium in calcined bentonite clay and clay after calcination and sodification (dispersed sodium clay) treatments. Adsorption isotherms were obtained at environmental temperature (25 oC). Langmuir, Freundlich and Dubinin-Radushkevich models were applied to fit the experimental data. It was observed an influence on the sodification treatment of the clay in its Cu2+ ion removal capacity, depending on the ion exchange mechanism involved.